Spatiotemporal Analysis of Marine Debris Existence in Parangtritis Coastal Area, Yogyakarta, Indonesia - Mardiatno, Djati; Wiratama, Herjuna (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2021)
This research is aimed to identify the marine debris types and their distribution based on morphological characteristic of the coastal area. It was conducted between Pantai Depok and Pantai Parangtritis, Yogyakarta. Specifically, the morphological identification was carried out to characterize the morphology of the location under study and its relation to the distribution of existing marine debris. This research used survey method, accompanied by systematic sampling techniques. Perpendicular line transects created in 100 meters intervals, accompanied by a 1x1 meter grid for marine debris identification. Descriptive qualitative analysis was done to explain the spatial temporal aspect of marine debris existence. The results of the study were presented in a cross-section morphological description, analysis table, and a map showing the distribution of marine debris along with a description of the type of debris and its density. The results showed that the distribution of marine debris was spatially clustered on the west side, especially on the coast of Depok. This fact reveals that the distribution of marine debris will indirectly follow the coastal morphology, i.e. the amount of debris will increase if it approaches the river mouth. Temporally, the highest amount of marine debris was obtained in March and the lowest was obtained in July. Degradable marine debris is dominated by wood, while non-degradable is dominated by plastics and straws. The greatest amount of marine debris occured during the west season, which indicates that the supply of debris coming from the Opak River, located in the western part of the study area.